Effect of foliar application of organic liquids on yield and quality of garlic (Allium sativum) (Current Horticulture, 2024)
The effect of foliar application of organic liquids on growth, yield and quality of garlic (Allium sativum L.) cv. Yamuna Safed-3”  was studied at Regional Horticultural Research Station, ASPEE College of Horticulture and Forestry, Navsari Agricultural  University, Navsari, Gujarat during rabi season (2019-20). The experiment was laid out in randomized block design with three  replications and nine treatments, viz. Panchagavya, novel plus, Jeevamrut and cow urine at each of 1% and 2% concentration  and the control (no spray). The foliar application of Panchagavya @ 2 % (T2) gave significantly maximum plant height (55.05 and  60.61 cm at 75 and 90 DAP, respectively), whereas maximum number of leaves/plant (7.0 and 8.13 at 75 and 90 DAP, respectively)  and minimum days to maturity (127.37 days) were also reported in novel plus @ 2 % (T4). The novel plus @ 2 % (T4) recorded  significantly maximum fresh weight of bulbs (24.79 g), dry weight of bulbs (16.73 g), diameter of bulb (3.75 cm), number of cloves/ bulb (18.60), weight of clove (2.16 g), length of clove (3.48 cm) and yield of bulbs (3.97 kg/plot and 7.87 t/ha). The plants sprayed  with novel plus @ 2 % (T4) recorded higher total soluble solids (16.87and 22.43 0Brix at 2 and 4 MAH, respectively), ascorbic acid  content (20.30, 18.30 and 15.97 mg at 2, 4 and 6 MAH, respectively) with maximum storage life of 219.67 days at room temperature.  However, maximum net income of ₹2,36,012/hawith a benefit: cost ratio of 3.00 was recorded in foliar spray of Novel plus @ 2 %  (T4) as compared to rest of the treatments.
Keywords: Garlic; Panchagavya; Novel plus; Jeevamrut; Cow urine and Foliar application